2020
DOI: 10.1590/1980-57642020dn14-030010
|View full text |Cite
|
Sign up to set email alerts
|

Memory training combined with 3D visuospatial stimulus improves cognitive performance in the elderly: pilot study

Abstract: ABSTRACT. Studies suggest that the engagement of aged participants in cognitive stimulation programs can reduce expected cognitive decline associated with age. Objective: To evaluate the effects of memory training (MT) associated with three-dimensional multiple object tracking (3D-MOT) NeuroTracker (NT) in the elderly. Methods: Forty-four participants (>60 years of age) were recruited and randomly distributed into two groups: experimental (EG; n=22) and comparative (CG; n=22). Both groups performed 12 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Similarly, other studies have shown cognitive benefits with different techniques in healthy older adults, regardless of their initial cognitive status [35][36][37][38][39][40][41][42][43][44][45]. This reflects a general view that lack of cognitive activity accelerates cognitive decline [46] and that cognitive stimulation could optimize cognitive function [47,48] producing an increase in neuronal volume [49].…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, other studies have shown cognitive benefits with different techniques in healthy older adults, regardless of their initial cognitive status [35][36][37][38][39][40][41][42][43][44][45]. This reflects a general view that lack of cognitive activity accelerates cognitive decline [46] and that cognitive stimulation could optimize cognitive function [47,48] producing an increase in neuronal volume [49].…”
Section: Discussionmentioning
confidence: 76%
“…This process enhances individual awareness as well as concentration and is estimated to ensure quick and precise decisions making, required to provide significant improvements. Besides, the phenomenon is observed especially in the aspect of attention, memory, information processing speed, and learning (17).…”
Section: Discussionmentioning
confidence: 99%